A combined sound field reconstruction method for large cylindrical surfaces using non-conformal plane measurement. (29th October 2021) - Cheng, Wei; Han, Shengming; Song, Chao; Nie, Zelin; Chen, Xuefeng; Zhang, Peng; Ni, Jinglei
Abstract: In practical acoustic measurement for large cylindrical surfaces, it is difficult to keep conformal and coaxial between the holographic surface and the reconstruction surface. To overcome this problem, a combined sound field reconstruction method using non-conformal plane measurement is proposed in this paper. Based on the sound pressure measured on the holographic plane, the combined method first reconstructs the sound field on the cylindrical conformal surface using statistically optimal planar near-field acoustic holography, and then reconstructs the sound field on the cylindrical reconstruction surface using statistically optimal cylindrical near-field acoustic holography. And a least square optimization method is proposed to determine the optimal position of the conformal surface. In addition, to overcome ill-posed problems, an error reduction method combining truncated singular value decomposition and Tikhonov regularization is proposed. Finally, the proposed method is applied to a test bed, and the accuracy and robustness of the sound field reconstruction for large cylindrical surfaces are obviously improved, which can provide reliable evidences for noise monitoring and control of mechanical systems.